HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG ANEMIA DENGAN KEJADIAN ANEMIA DI PUSKESMAS PORIAHA KABUPATEN TAPANULI TENGAH TAHUN 2020 - Maria Magdalena Saragi (Poltekkes Kemenkes Medan, 2024)
The most common anemia in pregnancy is anemia due to iron deficiency. Anemia during pregnancy can cause health problems during pregnancy or during childbirth. Serious disorders can cause death in the mother. Maternal deaths are related to pregnancy, childbirth and the postpartum period. Anemia in pregnancy can be detected by checking the Hb/Haemoglobin levels in the blood of pregnant women. The first examination is carried out before the 12th week of pregnancy and the 28th week. If the Hb level is <11 gr% in pregnancy, it is declared anemia and must be given iron tablet supplements regularly, 1 tablet/day for 90 days. This type of research is descriptive with an analytical survey method with a cross-sectional design with the aim of finding out the relationship between pregnant women's knowledge about anemia and the incidence of anemia. The number of samples is the total population, namely all 30 pregnant women who visited the Poriaha Health Center. Data collection was carried out by distributing questionnaires about anemia and checking the Hb of pregnant women. The results of the research showed that the majority of respondents had sufficient knowledge about anemia, namely 19 people (63.3%) and the minority of respondents had insufficient knowledge, namely 3 people (10.0%). It was found that the majority of pregnant women did not experience anemia, namely 18 people (60.0%) and the minority of respondents experienced anemia, namely 12 people (40.0%). So there is a significant relationship between the variable level of knowledge and the incidence of anemia at the Poriaha Community Health Center, Central Tapanuli Regency with a value of p = 0.041 < 0.05. The conclusion of this study is that there is a relationship between pregnant women's knowledge about anemia and the incidence of anemia. It is hoped that the Community Health Center will further improve services to pregnant women in dealing with the risk of anemia by providing health education to increase knowledge about anemia during pregnancy.